Rancang Bangun Sistem Monitoring Tinggi Muka Air di Wilayah Danau Toba - Maulana Putra; Dyah P. Djenal; Fajar Giri Suseno; Tiven Sandro (UM Purwokerto Press, 2021)
Lake Toba is a tecto-volcanic lake located in North Sumatra Province, Indonesia. Currently, Lake Toba is 1 (one) of 5 (five) Super Priority Tourism Destinations (DPSP) prepared by the Government of Indonesia. This study made a design for a water level monitoring system in the Lake Toba region. This system design is one form of mitigation, namely an effort to reduce disaster risk. The design of the Water Level Monitoring System in the Lake Toba Region used several components, namely Data Loggers, Sensors, and supporting equipment such as power supplies and communication systems. The Water Level Monitoring System in the Lake Toba Region was built in 6 (six) locations, namely Ajibata Port, Ambarita Port, Simanindo Port, Muara Port, Sippingan Port, and Balige Port. The observation of the monitoring system in the Lake Toba region showed that the water level and data quality vary. The sensor in this system can identify changes in water level in the Lake Toba region with a small amplitude of 10-15 centimeters.